Efektivitas Pembelajaran Problem Solving Berbantuan LKPD terhadap Keterampilan Pemecahan Masalah dan Penguasaan Konsep Biologi Siswa - Raudatul Jannah (AIJER: Algazali International Journal Of Educational Research, 2021)
Abstract: Effectiveness of LKPD-Assisted Problem Solving Learning on Problem Solving Skills and Mastery of Students' Biology Concepts.  This study aims to examine the effectiveness of active learning assisted by LKPD Problem Solving on problem-solving skills and mastery of biological concepts. This research method uses quasi-experiments. The research design used was the Control Group Pretest Posttest. The data collection techniques used are observation, interviews, documentation, and tests. The method of data analysis of problem-solving skills is by testing the normality of One Sample Kolmogorov-Smirnov and continuing the Mann Whitney U test, while the data analysis method is mastery of biological concepts with the Independent Sample T-Test with the SPSS 22 forwindows application. The results showed that the active learning model assisted by LKPD Problem Solving was effective in improving problem-solving skills with a significance value of 0.000 (p<0.05), and effectively increasing the value of students' biology concept gain by 0.62 or 62% with a moderate category and getting a significance value of 0.000 (p < 0.05).